2007
DOI: 10.1016/j.apnu.2007.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Residential Treatment for Prisoners With Mental Illness: A Follow-up Report

Abstract: The October 2002 issue of Archives of Psychiatric Nursing reported on the design of a prison-based mental health program implemented during the mid 1990s. The aim of this program was to reduce debilitating symptoms and promote coping skills, thereby enhancing both the functional status and clinical management of mentally ill prisoners. This article presents a qualitative study of the same program conducted in 2001−2003, and describes critical issues facing mental health providers, correctional officers, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Collaboration issues are frequently reported in correctional and forensic psychiatric settings (Brown & Lewis, 2015; Prebble et al, 2011) and it was no exception in this study. Diverging philosophies and approaches among staff (Brown & Lewis, 2015; Cloyes, 2007) inevitably accentuate the problem. IPT embraces a cognitive understanding of the behaviors of individuals with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaboration issues are frequently reported in correctional and forensic psychiatric settings (Brown & Lewis, 2015; Prebble et al, 2011) and it was no exception in this study. Diverging philosophies and approaches among staff (Brown & Lewis, 2015; Cloyes, 2007) inevitably accentuate the problem. IPT embraces a cognitive understanding of the behaviors of individuals with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…This situation is even more concerning in correctional and forensic psychiatric settings as the standards of care are not necessarily the same as for the general population (Dupuis et al, 2013; Kirby, 2006). Besides common barriers to the implementation of psychosocial approaches, these settings must deal with a dual mission of care and security (Brown & Lewis, 2015; Cloyes, 2007; O’Connor et al, 2002) as well as issues of coordination and continuity of care (Dupuis et al, 2013; Livingston, 2006). Furthermore, inmates and forensic patients have a distinctive clinical profile that has to be considered in psychosocial services provision (Dumais et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One potential pragmatic response to the issues facing prisons managing prisoners with SMI is the development of specialist units. A brief review of the international literature identified publications relating to a small number of specialist prison units: one located in England (Samele et al, 2016) and another in Ireland (Giblin et al, 2012;WHO, 2011), both of which admit prisoners with physical and mental health problems; two in the USA, which admit prisoners with mental health problems only (Cloyes, 2007;Kupers et al, 2009;O'Connor et al, 2002); and one in the Netherlands, which admits male remand and sentenced prisoners with mental illness or serious behavioral disorders (Blaauw et al, 2000;Council of Europe, 1993, 2015Tak, 2008). A number of key themes emerged from this literature.…”
Section: Specialist Prison Unitsmentioning
confidence: 99%
“…Secondly, the admission criteria ranged from challenging behavior, repetitive self-harm, 'mentally unwell', to SMIsome also included the need to demonstrate motivation to engage and likelihood of benefit. Thirdly, whilst treatment or interventions provided were not reported for the England or Ireland units, in the US units there were specific structured approaches and treatments including an 'Assertive Community Treatment' approach and a 'positive psychology' approach, as well as psycho-education and cognitive behavior treatment (Cloyes, 2007;Kupers et al, 2009;O'Connor et al, 2002).…”
Section: Specialist Prison Unitsmentioning
confidence: 99%
“…Services geared to offenders, and indeed the prison system itself, are not designed to recognize or accommodate gender-related difference (Chesney-Lind, 2006). Indeed, as we have argued elsewhere in relation to people with mental illness, a central tenet of corrections is that to maintain "safety, security, and integrity," everyone must be treated the same (Cloyes, 2007;Cloyes, Lovell, Allen, & Rhodes, 2006). This lack of recognition of gender-based differences is somewhat ironic because prisons have always been, and remain, deeply gendered institutions (Carlen & Worrall, 2004;Howe, 1994).…”
Section: Lack Of Gender-sensitive Programs and Researchmentioning
confidence: 99%